2011
DOI: 10.1093/toxsci/kfr072
|View full text |Cite
|
Sign up to set email alerts
|

Oversulfated Chondroitin Sulfate and OSCS-Contaminated Heparin Cause Dose- and Route-Dependent Hemodynamic Effects in the Rat

Abstract: During 2007-2008, serious adverse events were reported following iv administration of certain batches of commercially available heparin in humans. Anaphylactoid reactions with acute hypotension were the hallmark of these cases. Subsequently, it was shown that a contaminant, oversulfated chondroitin sulfate (OSCS), was responsible for these adverse events. The present study was undertaken to further elucidate the risks related to OSCS-contaminated heparin preparations. Using an anesthetized rat hemodynamic mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 18 publications
1
19
0
2
Order By: Relevance
“…It is likely that route of delivery, and the dose of the contaminated heparin delivered were factors contributing to the severity of the adverse events. These conclusions are supported by a rat study in which the hypotensive effects experienced by patients could be replicated in rats by intravenous delivery of OSCS-contaminated heparin, whereas subcutaneous administration was not effective, moreover, the hypotensive effect was dependent upon the concentration of the contaminating OSCS [ 147 ].…”
Section: Heparin Mimetics: Potential Toxicitiesmentioning
confidence: 86%
See 1 more Smart Citation
“…It is likely that route of delivery, and the dose of the contaminated heparin delivered were factors contributing to the severity of the adverse events. These conclusions are supported by a rat study in which the hypotensive effects experienced by patients could be replicated in rats by intravenous delivery of OSCS-contaminated heparin, whereas subcutaneous administration was not effective, moreover, the hypotensive effect was dependent upon the concentration of the contaminating OSCS [ 147 ].…”
Section: Heparin Mimetics: Potential Toxicitiesmentioning
confidence: 86%
“…Rather kallikrein induced by FXIIa appeared to be the key initiating factor [ 145 ]. When screening for contact system activation and high kallikrein activities the choice of plasma is important as animal plasmas have been reported to differ according to species in their capacity to give rise to the high kallikrein activities seen with human plasma following stimulation with OSCS [ 145 , 147 ]. Curiously a veterinary drug, polysulfated glycosaminoglycan (PSGAG) marketed as Adequan ® , also an oversulfated chondroitin sulfate, is administered intramuscularly for animal (dog and horse) osteoarthritis.…”
Section: Heparin Mimetics: Potential Toxicitiesmentioning
confidence: 99%
“…Because of the symptoms and the known ability of dextran sulfate to activate the contact system [3], research quickly focused on OSCS mediated activation of the contact system as a prime biochemical mechanism to link contaminated heparin with the adverse events. In subsequent research, OSCS was found to activate the kallikrein-kinin (KK) pathway in human plasma and this pathway was proposed to cause the production of vasoactive mediators such as bradykinin (BK) and the anaphylatoxins C3a and C5a in a factor XIIa (FXIIa) dependent manner [4][5][6][7][8]. Consistent with this hypothesis, OSCS alone and OSCS contaminated heparin induced hypotension in swine or rat blood pressure models [4,5,7].…”
Section: Introductionmentioning
confidence: 82%
“…For the BK pathway, Adam et al showed a direct dose response relationship between OSCS and BK production in plasma [6]. Subsequently, McKee et al and Corbier et al showed in rat models that OSCS induced hypotension was fully abolished by pretreatment with a specific BK-receptor 2 antagonist [4,7] and that OSCS induced KK activity in rat plasma [4]. For C5a, Kishimoto et al showed significant C5a production with OSCS contaminated heparin via a FXIIa-dependent mechanism in human plasma [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation